2008
DOI: 10.1111/j.1600-0528.2008.00433.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral health equality during 30 years in Norway

Abstract: The condition of edentulousness is a result of accumulated incidences of dental diseases and fragmented access to dental care. Economic barriers and unavailability of dental care postponed necessary restorative dental care and resulted in more drastic treatment solutions previously especially in the rural areas in Norway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
70
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 13 publications
5
70
2
4
Order By: Relevance
“…In particular, the general demographic transition and its impact on oral health (Harford, 2009) have attached special importance to tackling inequalities among elderly generations (Tsakos, 2011). Although the existence of such inequalities has been well-documented for many years (Watt and Sheiham, 1999;Locker, 2000;Gilbert et al, 2003;Sanders et al, 2006;Watt, 2007;Holst, 2008;Tsakos et al, 2009), we still do not comprehensively understand how such inequalities can best be reduced. Strategies for tackling oral health inequalities are increasingly being discussed within the context of a 'common-risk factor' approach (Sheiham and Watt, 2000;Sanders et al, 2005), which aims at addressing the joint causes of multiple common diseases, oral health impairment being just one of them (Marshman and Robinson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the general demographic transition and its impact on oral health (Harford, 2009) have attached special importance to tackling inequalities among elderly generations (Tsakos, 2011). Although the existence of such inequalities has been well-documented for many years (Watt and Sheiham, 1999;Locker, 2000;Gilbert et al, 2003;Sanders et al, 2006;Watt, 2007;Holst, 2008;Tsakos et al, 2009), we still do not comprehensively understand how such inequalities can best be reduced. Strategies for tackling oral health inequalities are increasingly being discussed within the context of a 'common-risk factor' approach (Sheiham and Watt, 2000;Sanders et al, 2005), which aims at addressing the joint causes of multiple common diseases, oral health impairment being just one of them (Marshman and Robinson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in other countries the prevalence of edentulousness was very low at 0.2-3%, suggesting that this condition is disappearing in Lithuania [Skudutyte et al, 2000], the Czech Republic [Broukal et al, 2006], Finland [Suominen-Taipale et al, 2008], Switzerland [Zitzmann et al, 2008], Norway [Holst, 2008], Hungary [Madléna et al, 2008], the Netherlands [Schuller, 2009], Turkey [Gökalp et al, 2010], Greece [Mamai-Homata et al, 2012], Belgium [Bottenberg et al, 2015], Portugal [Calado et al, 2015], and Germany [Jordan and Micheelis, 2016].…”
Section: Edentulousness In Adults and Senior Citizensmentioning
confidence: 99%
“…It has been well documented that there exists a socio-economic gradient in oral health, i.e., individuals from the lower end of the socio-economic scale usually have a worse oral health status than do individuals with higher socio-economic status (Watt and Sheiham, 1999;Locker, 2000;Gilbert et al, 2003;Enjary et al, 2006;Jamieson and Thomson, 2006;López et al, 2006;Makhija et al, 2006;Sanders et al, 2006;Tellez et al, 2006;Armfield, 2007;Watt, 2007;Holst, 2008;Du et al, 2009;Tsakos et al, 2009;Do et al, 2010;Ståhlnacke et al, 2010;Bernabé and Marcenes, 2010). While there is disagreement about the exact explanation for such a socio-economic gradient in oral health (Petersen, 2005;Brunner and Marmot, 2006;Sisson, 2007), it has frequently been suggested that dental attendance patterns are one pathway through which differences in oral health may emerge.…”
Section: Introductionmentioning
confidence: 99%